Religion, Culture, and Politics in Pre-Islamic Iran : Collected Essays - Lincoln, Bruce (Ancient Iran Series, 2021)
In Religion, Culture, and Politics in Pre-Islamic Iran , Bruce Lincoln offers a vast overview on different aspects of the Indo-Iranian, Zoroastrian and Pre-Islamic mythologies, religions and cultural issues. The book is organized in four sections according to the body of evidence they engage most directly: Avestan, Old Persian, Pahlavi, and Iranian materials in comparison with other data, including studies of myths, especially those with cosmogonic implications, ritual practices, cosmological constructions of space and time, points of intersection between religion, ethics, law, and politics, ideological aspects of scientific and medical theorizing, social organization and gender relations, and other diverse topics.